2021
DOI: 10.1021/acsabm.0c01627
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of Polypropylene Mesh with a Porcine Cholecystic Extracellular Matrix Hydrogel for Mitigating Host Tissue Reaction

Abstract: Polypropylene (PP) meshes are widely used for repairing skeletal muscle defects like abdominal hernia despite the chances of undesirable pro-inflammatory tissue reactions that demand revision surgeries in about 45% of cases. Attempts have been made to address the problem by modifying the mesh surface and architecture. These procedures have yielded only incremental improvements in the management of overall postoperative complications, and the search for a clinically viable therapeutic strategy continues. This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…24,28 Extracellular matrix coatings showed either negative or neutral impacts on collagen deposition, neovascularization, and tensile strength, yet they were beneficial for reducing inflammation and foreign body reactions. [31][32][33] Hydrogel and collagen coatings yielded mixed results, ranging from positive to no significant differences. 36,37,39,41 Chitosan, a resorbable coating, showed no biomechanical response in two studies, but one study reported improvements in collagen deposition, neovascularization, inflammation, and foreign body reaction.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…24,28 Extracellular matrix coatings showed either negative or neutral impacts on collagen deposition, neovascularization, and tensile strength, yet they were beneficial for reducing inflammation and foreign body reactions. [31][32][33] Hydrogel and collagen coatings yielded mixed results, ranging from positive to no significant differences. 36,37,39,41 Chitosan, a resorbable coating, showed no biomechanical response in two studies, but one study reported improvements in collagen deposition, neovascularization, inflammation, and foreign body reaction.…”
Section: Resultsmentioning
confidence: 98%
“…The studies used different test subjects: five used mice, 19-23 36 rats, 24-59 eight rabbits, 60-67 one dogs, 68 two pigs, 69,70 and six used humans. 10,12,71-74 The studies comprised a total of 408 humans and 2679 animals.…”
Section: Resultsmentioning
confidence: 99%
“…Ganjalinia et al reported PP with a Lactic acid-based mat for use as a scaffold in the body [ 41 ]. Also, a mesh with PP, after modifying its surface, has been prepared for the preparation of biomedical devices [ 42 ]. PP/CNT and hydroxyapatite nanocomposite in human subchondral bone are produced by Khan et al [ 43 ].…”
Section: Pp Membranementioning
confidence: 99%
“…It dramatically reduced collagen deposition and increased angiogenesis, promoting the regeneration of natural tissues. Raj et al attenuated the adverse tissue reaction induced by PP mesh by dip-coating the mesh with a hydrogel formulation of porcine gallbladder ECM. In a rat model, C-PP attenuated the tissue response and reduced the number of pro-inflammatory M1 macrophages and cytotoxic lymphocytes compared to PP mesh, resulting in an altered fibrotic response that facilitated the repair of tissue defects.…”
Section: Strategies For Reducing Postoperative Complicationsmentioning
confidence: 99%